A Study of Post - Colonialism in Toni Morrision Works (International Journal of Scientific Research in Science and Technology, 2024)
Toni Morrison, a literary giant of the 20th century, has left an indelible mark on American literature. Her body of work, often celebrated for its lyrical prose and profound exploration of African American experiences, delves deeply into the post-colonial context of the United States. This article will examine how Morrison’s novels and essays engage with post-colonial themes, offering a unique perspective on the enduring legacy of colonialism and slavery. The present paper attempts to explore postcolonial thinking through a study of post colonialism in the works of Toni Morrison. The vast term post colonialism is presented in small areas. Toni Morrison’s exploration of post-colonialism is an integral part of her literary legacy. Her works challenge readers to confront the uncomfortable truths of history and encourage discussions on the enduring effects of colonialism and slavery. Morrison’s storytelling prowess and commitment to representing the African American experience make her an essential figure in the ongoing dialogue about post-colonialism in literature. In the article, we are going to discuss the literary brilliance and quest for ideology, justice, and healing from postcolonial perspectives in the works of Toni Morrison. The present paper is attempted to explore on “A Study of Post-Colonialism in Toni Morrison’s Selected Works.